Формообразование при химическом мутагенезе у лилейника гибридного - Крохмаль, И.И. (Промышленная ботаника, 2006)
Morphogenesis peculiarities of seedlings of Hemerocallis hybrid ′Date of Book′ in F1 on the nitrosoethylcarbamid (NEC) mutagen impact were studied. Four perspective seedlings for selection were singled out as a control. Three perspective seedlings were singled out under 0,1% NEC impact with 3 h exposition in the first trial variant and one seedling – under 0,05% NEC effect with 3 h exposition in the second one. The most amplitude of change of phenotypic characters was indicated in the first trial variant.